Saxagliptin add‐on therapy in Chinese patients with type 2 diabetes inadequately controlled by insulin with or without metformin: Results from the SUPER study, a randomized, double‐blind, placebo‐controlled trial. Issue 4 (18th December 2017) - Chen, Yingli; Liu, Xiaomin; Li, Quanmin; Ma, Jianhua; Lv, Xiaofeng; Guo, Lixin; Wang, Changjiang; Shi, Yongquan; Li, Yanbing; Johnsson, Eva; Wang, Mei; Zhao, June; et al.
Abstract : This prospective, multicentre, phase III study (NCT02104804) evaluated the efficacy and safety of saxagliptin add‐on therapy in Chinese patients with type 2 diabetes inadequately controlled by insulin ± metformin. Patients with glycated haemoglobin (HbA1c) 7.5% to 10.5% and fasting plasma glucose (FPG) <15 mmol/L (270 mg/dL) on stable insulin therapy (20‐150 U/d) were randomized (1:1) to saxagliptin 5 mg once daily ( N = 232) or placebo ( N = 230) for 24 weeks, stratified by metformin use. The primary efficacy measure was change in HbA1c. Saxagliptin treatment resulted in a greater adjusted mean change in HbA1c from baseline to week 24 than placebo (−0.58%; P < .001), irrespective of metformin use, and a greater mean change in FPG (0.9 mmol/L [−15.9 mg/dL]; P < .001). More patients achieved HbA1c <7% with saxagliptin (11.4%) than with placebo (3.5%, P = .002). Adverse events and incidence of hypoglycaemia were similar in both groups. Overall, add‐on saxagliptin 5 mg once daily significantly improved glycaemic control without increasing hypoglycaemia risk and was well tolerated in Chinese patients with type 2 diabetes inadequately controlled by insulin (± metformin).